FROM JEAN CALAS’ SENTENCE TO FAKE NEWS: WHAT VOLTAIRE TELLS US ABOUT MEDIA TOLERANCE IN OUR DAYS - de Lima Pacheco, Marcio; Chagas Ramos, Rawy (Revista Gênero e Interdisciplinaridade, 2023)
This article is an excerpt from the research on Discourse Analysis in the media and fake news: the disinformation that destroys lives and from the Tinder Olympics: An analysis of the Construction of Ethos in the Promotion of the Self from Dominique Maingueneau. It investigates the importance of media tolerance in the digital age, focusing on the case of Jean Calas, a French merchant who was tried and killed for untrue news, and Voltaire’s ideas about liberty and equality. Analyzes how fake news and False information on social media impacts fairness and tolerance. The work uses literature review and analysis of recent cases to explore ways to promote responsible media tolerance, emphasizing the importance of not being passive in the face of injustices or human rights violations. The results indicate that challenges of intolerance, exacerbated by social media, persist. The analysis highlights the seriousness of the consequences of the spread of disinformation and information and false information, to show the importance of developing critical skills to protect democracy and human rights. The need for critical and conscious education to verify information and promote dialogue and tolerance. The study also addresses the historical and politico-religious context of 17th century France, illustrating the consequences of religious intolerance and Voltaire’s struggle for justice in the case of Jean Calas. The lack of academic studies on fake news and the platforms that facilitate its circulation is discussed. The article concludes by emphasizing the continued relevance of the struggle for tolerance, especially on social media, and the need for an informed and responsible approach to build a just and equitable society by combating disinformation and promoting peaceful coexistence in a diverse and connected world.